2022
DOI: 10.1371/journal.pone.0262234
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and prognostic significance of novel ferroptosis-related genes in soft tissue sarcoma

Abstract: Background Ferroptosis has exhibited great potential in the treatment of cancer and has gained widespread attention in soft tissue sarcoma (STS). The aim was to explore the immunological and prognostic significance of novel ferroptosis-related genes in STS. Methods We identified ferroptosis-related differentially expressed genes (DEGs) in STS to construct the networks of enrichment analysis and protein-protein interaction. Subsequently, hub genes with prognostic significance were localized and a series of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It should be noted that the role of CENPA in ferroptosis has been rarely reported. However, STMN1 has been reported to as an important ferrGene in coronary artery disease, 45 soft tissue sarcoma, 46 adrenocortical carcinoma. 47 Similarly, the research of Wang et al 48 exhibited that STMN1 was a ferrGene that correlated to the poor survival of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the role of CENPA in ferroptosis has been rarely reported. However, STMN1 has been reported to as an important ferrGene in coronary artery disease, 45 soft tissue sarcoma, 46 adrenocortical carcinoma. 47 Similarly, the research of Wang et al 48 exhibited that STMN1 was a ferrGene that correlated to the poor survival of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ferroptosis, a novel iron-dependent lipid peroxidation induced RCD, was recently identified and found to be greatly involved in tumorigenesis (41). Evaluation of the prognostic value of ferroptosis-related genes has been widely performed in various tumors, such as pancreatic cancer, bladder cancer, colon cancer, hepatocellular carcinoma, glioblastoma, soft tissue sarcoma, thyroid papillary carcinoma, gastric cancer, ovarian cancer and so on (42)(43)(44)(45)(46)(47)(48)(49)(50). Associations between ferroptosis-related genes and TME have also been investigated in multiple cancers, including breast cancer, hepatocellular carcinoma, clear cell renal cell carcinoma, lung adenocarcinoma, head and neck squamous cell carcinoma, melanoma, papillary thyroid carcinoma and so on (51-57).…”
Section: Discussionmentioning
confidence: 99%
“…GO and KEGG enrichment analyses have uncovered that FRGs are significantly enriched in pathways related to cancer and the immune system. Correlation analyses of key FRGs with immune checkpoint genes (ICGs) have revealed positive associations between the expression levels of CXCL2 and IL6, which are proteins encoded by FRGs, and the expression of immune factors [ 235 ]. RIPK1, a key FRG, has also been shown to be part of the same protein interaction network as immune checkpoints like PD-1 [ 239 ].…”
Section: Progress Of Research On Ferroptosis In Sarcoma Treatmentmentioning
confidence: 99%
“…RIPK1, a key FRG, has also been shown to be part of the same protein interaction network as immune checkpoints like PD-1 [ 239 ]. Furthermore, prognostic analyses based on FRGs have demonstrated that different risk groups exhibit varying patterns of immune cell infiltration, and individuals with more active immune cell involvement tend to have a better prognosis [ 9 , 235 , 237 ]. These findings suggest that FRG-encoded proteins can influence tumor prognosis by modulating the immune system, and further support the relationship between ferroptosis and tumor immune system.…”
Section: Progress Of Research On Ferroptosis In Sarcoma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation